KATA·DAN MUSIKDALAM KEGIATAN BERMAIN SEBUAH AKTIVITAS YANG MENDORONG PERKEMBANGAN OTAK PADA ANAK USIA DINI - Wulandari, Rina (MAJALAH ILMIAH PEMBELAJARAN, 2007)
There are many forms of children ’s game in early childhood education. Many of them give children advantages specifically in brain development. To children, playing is a serious bu1 fim thing. MW!Y works are done through playing. Children choose to play not in the purpose of complements or presents but merely beca:1se ii is fun. Playing is the main instrument to exercise for their gro1tth. Playing is a medium, where students make experiments, not only in their mind but for real. Whenever children play freely in their own willingness and capaciry, they are exercising. Playing with music that is intended to introduce language to children is one example ofjoyfal learning. This paper briefly exp/Jin techniques on joyful learning that in the end is expected w bring advantage for children’s development as the author stated above.